Biological conversion of biogas to methanol using methanotrophs isolated from solid-state anaerobic digestate. (February 2016) - Sheets, Johnathon P.; Ge, Xumeng; Li, Yueh-Fen; Yu, Zhongtang; Li, Yebo
Highlights: Methanotrophs were isolated from solid-state anaerobic digestate. Both biogas and purified methane were suitable substrates for methanotrophs. Biogas from a commercial anaerobic digester was biologically converted to methanol. Several methanol dehydrogenase inhibitors promoted methanol production. Methanol production increased 4-fold to 22-fold using formate as an electron donor. Abstract: The aim of this work was to isolate methanotrophs (methane oxidizing bacteria) that can directly convert biogas produced at a commercial anaerobic digestion (AD) facility to methanol. A methanotrophic bacterium was isolated from solid-state anaerobic digestate. The isolate had characteristics comparable to obligate methanotrophs from the genus Methylocaldum . This newly isolated methanotroph grew on biogas or purified CH4 and successfully converted biogas from AD to methanol. Methanol production was achieved using several methanol dehydrogenase (MDH) inhibitors and formate as an electron donor. The isolate also produced methanol using phosphate with no electron donor or using formate with no MDH inhibitor. The maximum methanol concentration (0.43 ± 0.00 g L −1 ) and 48-h CH4 to methanol conversion (25.5 ± 1.1%) were achieved using biogas as substrate and a growth medium containing 50 mM phosphate and 80 mM formate.